2022
DOI: 10.3390/mi13122097
|View full text |Cite
|
Sign up to set email alerts
|

Citrate Functionalized Zirconium-Based Metal Organic Framework for the Fluorescent Detection of Ciprofloxacin in Aqueous Media

Abstract: Ciprofloxacin (CIP) is a commonly used antibiotic for the treatment of infectious diseases in humans and as a prophylactic agent in the livestock industry, leading to the environmental discharge of significant amounts of CIP. CIP is stable in aquatic systems leading to its pseudo-persistence. Constant exposure to these antibiotics results in the generation of antibiotic-resistant pathogens and potential toxicity/hypersensitivity in humans. Therefore, it is necessary to develop a convenient, rapid, and cost-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…However, the toxic nature of lanthanides can limit their application for real-field monitoring. Liu et al reported the Zr-based MOF functionalized with citrate (C-MOF-808) for the fluorescent detection of ciprofloxacin in aqueous solutions [11]. Beside the high sensitivity of these fluorescent sensors, their combination with molecularly imprinted polymers (MIPs) can offer specific target detection capabilities [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the toxic nature of lanthanides can limit their application for real-field monitoring. Liu et al reported the Zr-based MOF functionalized with citrate (C-MOF-808) for the fluorescent detection of ciprofloxacin in aqueous solutions [11]. Beside the high sensitivity of these fluorescent sensors, their combination with molecularly imprinted polymers (MIPs) can offer specific target detection capabilities [12,13].…”
Section: Introductionmentioning
confidence: 99%